Assessing The Impact Of Digital Communication On Language Processing - Austin, Wahyu; Achmad Nurcholish, Ivan (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2025)
Language, as a tool of human communication, develops with time and technology. The use of language, especially in abusive forms, is increasing on social media and online gaming, creating an environment detrimental to mental health. The development of digital technology plays an important role in this change, influencing psycholinguistic aspects such as Stuttering and Psychogenic symptoms. In the context of politics and social media, abusive language is used as a tool to convey opinions, creating conflict and tension. While the internet brings positive transformations in learning, ineffective use can lead to distraction and exposure to less controlled information. Evaluation of student psychomotor skills is key to understanding the impact of internet use in learning. Through this research, the aim is to explore the impact of digital communication on language processing, especially from a psycholinguistic perspective. Empirical findings and further research are needed to understand more deeply the complexity of the impacts of technology, both negative and positive. Full awareness of how to manage the internet is the key to minimizing negative impacts and increasing its benefits in various aspects of life.